Impact of Mandatory Corporate Social Responsibility on Beneficiary Institutions Satisfaction in Nepal - Wagle, Sudip (BMC Journal of Scientific Research, 2023)
Corporate Social Responsibility (CSR) became mandatory legislation since 2016/17, in Nepal. The aim of this study is to determine the beneficiary institutions satisfaction from the companies CSR activities in Nepal. Descriptive and causal comparative research design was applied. For that, structured questionnaires were used among 400 registered beneficiary institutions. Mean, standard deviation, correlation and regression analysis were performed by using IBM SPSS 25 version software. The results of this study showed a significant positive correlation between corporate CSR initiatives and the satisfaction of beneficiary institutions in Nepal. Out of eight parameters, three variables make a statistically positively significant contribution (p-value<0.05) in beneficiary institutions satisfaction. The concern variables are company routinely visits the community through different CSR projects (BEN-CV). In case of any tear, wear, or depreciation in the community, assure the local company of their involvement (BEN-CI) and, companies conduct CSR programs for the uplifting community, from problems to prosperity (BEN-PP), whose beta value are 0.178, 0.171, and 0.373 respectively. Moreover, these days companies CSR program is more effective to the beneficiaries that play a meaningful role in society for nation’s sustainable development.